Joint optimisation on maintenance policy and resources for multi-unit parallel production system. (September 2021) - Gao, Wenke; Yang, Tianshu; Chen, Le; Wu, Shaomin
Highlights: A modelling method is presented for the Multi-unit parallel production systems. The method can depict the cycle operating process to be a mono-periodic diagram. A joint optimisation of maintenance, repairmen and spare units is proposed. An approach is developed to determine the displacement sequence for spare units. A real case study of train working line is presented using the proposed model. Abstract: Multi-unit parallel production systems (MuPPSs) widely exist in many industry areas. A general requirement for the MuPPS is that each production system should continuously run and its downtime should be as short as feasible. For such systems, optimising preventive maintenance (PM) policy is crucial so that resources such as the number of spare units and that of repairmen can be optimally used. On this basis, this paper develops an optimal model jointly optimising the PM policy and the number of repairmen and spare units, for which the genetic algorithm is used to determine the optimal displacement sequence of spare units. According to the developed model, a real case study of a train working line is presented to demonstrate its necessity. Finally, the sensitivity analysis is conducted to assess the influence of some parameters on the optimal results.